Pengaruh Audit Delay Terhadap Reaksi Investor Dengan Pengumuman Right Issue Sebagai Variabel Moderasi - Putri, Amanda; Suyanto, Suyanto; Padwa Sari, Gustin (Universitas Muhammadiyah Metro, 2025)
The purpose of this study was to analyze the effect of audit delay on investor reactions with rights issue as a moderating variable in manufacturing companies in the basic and chemical industry sectors listed on the IDX in 2021-2023. This research uses a quantitative approach. The sampling technique used purposive sampling method in manufacturing companies in the basic and chemical industry sectors in 2021-2023 and resulted in 65 data. The data analysis technique used is panel data linear regression analysis using eviews 12. Based on the results of data testing, it can be seen that audit delay has no partial effect on investor reactions. Meanwhile, the right issue is unable to moderate the relationship between audit delay and investor reaction.